Peran Dosen Wirausaha dalam Meningkatkan Motivasi Wirausaha di Kalangan Mahasiswa - Lena Ahdiani Hayati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The purpose of PKM activities is to develop learning methods for community education by conducting practice/experience-based entrepreneurship counseling. Partners who are the venue for the activity are students and the general public in Cigugur Village, Kuningan District, Kuningan Regency. PKM is based on initial research on partners where partners are still less interested in entrepreneurship, there are also no outside parties who carry out more in-depth counseling, including the practice of opening new businesses. which will be initiated. The method used for partners is counseling activities. Counseling is carried out by means of lectures, discussions, and questions and answers. Socialization about entrepreneurial motivation assisted by students as hosts where the village hall is a place for counseling. The debriefing materials that were told to partners in the form of PPT about increasing entrepreneurial motivation and others were prepared by the PKM team consisting of a team of lecturers and assisted by students. The result of the socialization activity organized by the PKM team is that the community and student participants understand that they can motivate themselves to produce creative and innovative ideas when dealing with sticky rice so that their business can always grow. The community and students have been able to recognize the potential they have and their surroundings. The community and students also understand the entrepreneurship needed to run a business or business